Effect of Organic Matter on Adsorption and Persistence of Thiram Fungicide in Different Soils - Kumar Srivastava, Ritesh; K. Singh, Brijesh; Mani, Dinesh (Asian Journal of Chemistry, 2012)
The Freundlich equation provides a good fit (r2 > 0.99) for the adsorption data on thiram in all the soils. The Freundlich constant (K) value for thiram in Farm Yard Manure (FYM) treated soils were more than in corresponding untreated soils. Thiram showed 'L' type isotherm curve (1/n < 1) indicated non-linear relationship between the thiram concentration and adsorption. The negative magnitude of Gibbs free energy (DG) indicate that the adsorption was exothermic and spontaneity process. The persistence of thiram indicated a close correspondence to the (r2 > 0.92) first order exponential degradation kinetics in the soils and mainly influenced by soil organic matter. The half-life (T1/2) value of thiram was highest for alluvial soil followed by sandy loam and black soils.